Предмет:
АлгебраАвтор:
corbinwaltersОтвет:
1
A) tg(x) * ctg(x) - sin^2(x) = 1 - sin^2(x) = cos^2(x)
B) cos^2(x) - 1/cos^2(x) = (cos^4(x) - 1)/cos^2(x)
2
A) cos^4(x) - sin^4(x)/cos^2(x) + 2tg^2(x) = (cos^2(x) + sin^2(x))(cos^2(x) - sin^2(x))/cos^2(x) + 2(sin^2(x)/cos^2(x)) = (1 - sin^2(x))/cos^2(x) + 2(sin^2(x)/cos^2(x)) = 1/cos^2(x)
Б) tg(x)/(tg(x) + ctg(x)) = tg^2(x)/sin(x)cos(x) + 1 = sin^2(x)cos^2(x)/sin(x)cos(x) + 1 = sin(x)cos(x) + 1
3
A) sin(210) = sin(180 + 30) = -sin(30) = -1/2
Б) ctg(13π/4) = ctg(π/4) = 1
С) cos(-765) - sin(-405) = cos(-360 - 405) - sin(-360) = cos(-45) - sin(45) = 1/√2 - 1/√2 = 0
Объяснение:
Автор:
daphnerkblВідповідь:
1)A) Не указаны аргументы функций, поэтому неясно, что нужно упрощать.
B) cos^2 - 1/cos^2 = (cos^4 - 1) / cos^2 = sin^2 / cos^2
2)A) cos^4 - sin^4 = (cos^2 + sin^2)(cos^2 - sin^2) = cos^2 - sin^2
cos^2 - sin^2 / cos^2 + 2tg^2 = (cos^2 - sin^2) / cos^2 + 2(sin^2 / cos^2) = (cos^2 - sin^2 + 2sin^2) / cos^2 = 1 / cos^2
Б) tg / (tg + ctg) = sin / (1/cos + cos/sin) = sin^2 / (cos + cos^2) = sin^2 / (cos^2 + cos) = sin^2
3)А) sin(210) = sin(180 + 30) = -sin(30) = -1/2
Б) ctg(13π/4) = ctg(π/4) = 1
С) cos(-765) - sin(-405) = cos(3π/4) + sin(45) = -sqrt(2)/2 + sqrt(2)/2 = 0
Пояснення:
Автор:
yairb6uoДобавить свой ответ
Предмет:
БиологияАвтор:
bennett637Ответов:
Смотреть
Предмет:
Английский языкАвтор:
terrancecabreraОтветов:
Смотреть
Предмет:
Українська моваАвтор:
serenityalexanderОтветов:
Смотреть
Предмет:
Українська літератураАвтор:
zaidenОтветов:
Смотреть